Light - Friedhoffer, Robert; Eisenberg, Linda; Kaufman, Richard; White, Timothy (New York : F. Watts, 1992)
Experiments, magic tricks, and other activities explore the scientific principles of light.
Includes bibliographical references (p. 104) and index.
Book Report.
Booklist.
6.4
5-7.
5-8
Keywords: Light -- Experiments -- Juvenile literature; Scientific recreations -- Juvenile literature; Experiments; Light -- Experiments; Magic tricks; Scientific recreations; Light -- Experiments; Magic; Scientific recreations